2015
DOI: 10.1016/j.gaceta.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years trends and socio-demographic characteristics of HIV prevalence in women giving birth in Catalonia (Spain)

Abstract: To ensure early identification and treatment of HIV-infected mothers, it is essential to maintain HIV surveillance programs and pre- and post-natal screening programs, both in Barcelona and in cities with 200,000 inhabitants or less, especially in immigrant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results of HTLV-1 testing of pregnant women in Spain during 2022 showed that prevalence rate has remained stable for two decades. 48,49 However, among Latin American pregnant women was 0.4%, a rate higher than that observed for other infections such as HIV (0.1%−0.26%) 50 or syphilis (0.11%), 51 almost fully stopped avoiding breastfeeding, 53 universal HTLV screening of pregnant women in Spain seems to be justified.…”
Section: Hiv-2 Epidemicsmentioning
confidence: 85%
See 1 more Smart Citation
“…The results of HTLV-1 testing of pregnant women in Spain during 2022 showed that prevalence rate has remained stable for two decades. 48,49 However, among Latin American pregnant women was 0.4%, a rate higher than that observed for other infections such as HIV (0.1%−0.26%) 50 or syphilis (0.11%), 51 almost fully stopped avoiding breastfeeding, 53 universal HTLV screening of pregnant women in Spain seems to be justified.…”
Section: Hiv-2 Epidemicsmentioning
confidence: 85%
“…The results of HTLV‐1 testing of pregnant women in Spain during 2022 showed that prevalence rate has remained stable for two decades 48,49 . However, among Latin American pregnant women was 0.4%, a rate higher than that observed for other infections such as HIV (0.1%−0.26%) 50 or syphilis (0.11%), 51 for which screening is mandatory during pregnancy. In the last 10 years, the number of Latin American women of childbearing age in Spain has risen from 40 385 to 109 479, which represents a 2.7‐fold increase.…”
Section: Interventions Toward the Elimination Of Human Retroviral Epi...mentioning
confidence: 99%